PENGARUH NET PROFIT MARGIN, RETURN ON ASSET, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN KONSTRUKSI DAN PROPERTI YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA - Muhammad Ichwan Hamzah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
This study was conducted with the aim of examining the effect of Net Profit Margin,Return On Assets, Return On Equity and Earning Per Share on stock prices in construction andproperty companies listed in the LQ45 index on the Indonesia Stock Exchange ”. The method of datacollection is done by using financial reports. This study uses 6 samples of construction and propertycompanies listed in the LQ45 Index. The period used in this research is 6 years starting from 2012-2017. The sample method used was purposive sampling (conditional sampling). The results showthat simultaneously it can be seen that the effect of Net Profit Margin, Return On Asset, Return OnEquity, and Earning Per Share on stock prices shows a significant value for the F test of 0.000111<0.05 (α = 5% ). The effect of Net Profit Margin, Return On Asset, Return On Equity and Earning PerShare on stock prices in construction and property companies listed in the LQ45 index on theIndonesia Stock Exchange